2010
DOI: 10.1128/aem.01902-09
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Survival ofCampylobacterSpecies in Bovine Manure Compost

Abstract: The persistence of naturally occurring campylobacteria in aerobic compost constructed of manure from beef cattle that were administered chlortetracycline and sulfamethazine (AS700) or from cattle not administered antibiotics (control) was examined. Although there were no differences in population sizes of heterotrophic bacteria, the temperature of AS700 compost was more variable and did not become as high as that of control compost. There were significant differences in water content, total carbon (C), total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 34 publications
(59 reference statements)
1
35
0
2
Order By: Relevance
“…The soil was first incubated using ethidium monoazide bromide (EMA) to prevent the amplification of DNA from nonviable cells (Pisz et al 2007). EMA has been used in a variety of studies to differentiate between viable and non-viable organisms in a variety of environments (Cenciarini-Borde et al 2009;Delgado-Viscogliosi et al 2009;Inglis et al 2010). EMA can intercalate double-stranded DNA and prevent its replication during PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The soil was first incubated using ethidium monoazide bromide (EMA) to prevent the amplification of DNA from nonviable cells (Pisz et al 2007). EMA has been used in a variety of studies to differentiate between viable and non-viable organisms in a variety of environments (Cenciarini-Borde et al 2009;Delgado-Viscogliosi et al 2009;Inglis et al 2010). EMA can intercalate double-stranded DNA and prevent its replication during PCR.…”
Section: Methodsmentioning
confidence: 99%
“…Campylobacter spp. are capable of surviving in bovine manure for a 10-month period (Inglis et al 2010). …”
Section: Ecology Ecology Of Campylobactermentioning
confidence: 98%
“…The approach is made possible by EMA's efficiency to penetrate dead cells even at relatively low dye concentrations. Whereas early studies employing EMA typically used final dye concentrations of 100 μg/ml (238 μM) (Douglas Inglis et al, 2010;Flekna et al, 2007;Graiver et al, 2010;Marouani-Gradi et al, 2010;Rudi et al, 2005a), concentrations in more recent studies were chosen substantially lower. Cawthorn and Witthuhn (2008) have found that the use of three different EMA concentrations with viable Enterobacter sakazakii cells − 100 (238 μM), 50 (119 μM), and 10 μg/ml (23.8 μM) -resulted in very different PCR product yields of 74, 82 and 92%, respectively (compared with 95, 96, and 97% after PMA treatment).…”
Section: Emamentioning
confidence: 99%